Synthetic population generation using census data - Darda, Abu; Khan, Rahat; Raad, Ashabul Yamin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.